The high-frequency response of energy prices to monetary policy: Understanding the empirical evidence - Carlo Rosa (Federal Reserve Bank of New York, 2013)
This paper examines the impact of conventional and unconventional monetary policy on energy prices, using an event study with intraday data. Three measures for monetary policy surprises are used: 1) the surprise change to the current federal funds target rate, 2) the surprise component to the future path of policy, and 3) the unanticipated announcements of future large-scale asset purchases (LSAPs). Estimation results show that monetary policy news has economically important and highly significant effects on the level and volatility of energy futures prices and their trading volumes. I find that, on average, a hypothetical unanticipated 100 basis point hike in the federal funds target rate is associated with roughly a 3 percent decrease in West Texas Intermediate oil prices. I also document that, in a narrow window around the Federal Open Market Committee meeting, the Federal Reserve's LSAP1 and LSAP2 programs have a cumulative financial market impact on crude oil equivalent to an unanticipated cut in the federal funds target rate of 155 basis points. Monetary policy affects oil prices mostly by affecting the value of the U.S. dollar exchange rate. Intraday energy prices also respond to news announcements about the U.S. macroeconomy and inventories. The daily responses are never significant, except in the case of inventory news.
Keywords: C01; E50; 330; monetary policy; federal funds futures; macroeconomic news; inventory news; oil futures